Study on current status of water quality and heavy metals at Tasik Chini in 2013 and 2019 during dry season - Yahya Alshaeer, Hanin Ali (2019)
The purpose of this study is to analyses water quality and determine the concentration of heavy metals in Tasik Chini lake. This study was conducted at 4 sampling stations in 2019 which are Sg.Jemberau , Sg.Jeranking , Sg.Gumum and Sg.Melai all stations are during dry season . A total of 13 water quality parameters and 12 heavy metals were measured and classified based on the Interim National Water Quality Standard of Malaysia (INWQS). The measured and analyzed parameter variables were divided into three main categories which are Physical, Chemical and Heavy metals contents. Physical and Chemical parameter variables were Temperature, Dissolved oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Turbidity, pH, Nitrate(N), Phosphate(P), Ammonia Cal Nitrogen (NH3-N), Conductivity (EC), Temperature, and Potassium (K). was analysis in-situ and laboratory experiments.Twelve parameters to identify heavy metals concentration are Iron (III) Oxide (Fe203), Silicon Dioxide (SiO2), Aluminum Oxide (Al203), Manganese Oxide (MnO), Potassium Oxide (K20), Titanium Dioxide (TiO2), Phosphorus pent oxide (p205), Barium Oxide (BaO),Lead Oxide (Pbo), Calcium Oxide (Cao), Sculpture Trioxide(SO3), and Zinc Oxide (ZnO) also had test by run ICP-MS. Five parameters of heavy metals concentration to be tested iv this reeserch which are Cadmium (Cd), Copper (Cu), Chromium (Cr), Zinc (Zn)and Lead (Pb) were tested by using Atomic Absorption Spectroscopy (AAS).The result also indicates that the Tasik Chini water are not polluted in this study with heavy metals since all heavy metal readings were recorded below Class I, which suitable for conservation of natural environment and very sensitive aquatic species. However, illegal logging, iron mining, industrial and agriculture activities in surrounding of the lake consequently affected the pollution of water at Tasik Chini. Results based on Malaysian WQI have shown that the water in Tasik Chini is classified as Class III, which can be used for recreational activities. Based on the land use observations done during site visits and yearly assessment using Google Earth application, the illegal logging, iron mining, industrial and agriculture activities in the surrounding area of the lake significantly affected the water quality of Tasik Chini.